النظرية السيميائية مقولاتها وافاقها التطبيقية - الأوسي، سلام كاظم; الشرع، آلاء حسين داوود (جامعة القادسية - كلية الآداب, 2005)
تعد السيمولوجيا واحدة من المناهج التي برزت في القرن العشرين وامتزجت بالعلوم الطبيعية الأخرى على أن جذور هذا المنهج وجد أثره في الدراسات النقدية القديمة، حيث ذكرت المفاهيم والمعنى التالي وعدت أساسا لعملية التداخل الدلالي أو ما تسمى بالسمقطة بالمفهوم الحديث ثم تطور المفهوم في العصر الحديث ليشكل منهجا ونظاما له أسسه وقوانينه التي جاءت على أنقاض البنيوية في الحركة الجديدة التي يطلق عليها اسم (ما بعد البنيوية). Symology is one of the methods which come out in the beginning of the twentieth century and mingled with the other natural sciences. The roots of this method affect the old critical studies which study the meaning and the following meaning, and they are considered the essence of the interpenetration process or what is called "Samkata" in the modern concept. Then this concept has developed in the modern age to form a method and a discipline which has its bases and laws which come on the ruins of the structural in the new movement that is called "After the Structural
Keywords: السيميائية في الأدب العربي; الأدب العربي; السيميائية